2007
DOI: 10.1080/13854040500519752
|View full text |Cite
|
Sign up to set email alerts
|

Executive Control Functioning and Functional Ability in Older Adults

Abstract: The manner in which executive control functioning exerts its influence on functional tasks was investigated. Sixty older adults were administered neuropsychological tasks tapping into four domains of executive control function, including working memory, planning, fluency, and flexibility. A test of performance-based functional ability also was administered. Correlational analyses demonstrated that working memory was most strongly associated with performance-based functional ability; however, impairment in plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
38
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 24 publications
2
38
1
Order By: Relevance
“…We also extend Smits et al (1997) by incorporating comparison tests of executive functions, which prior studies show are among the most reliable cognitive predictors of IADL in older adults (e.g., Lewis & Miller, 2007). Importantly, PM was predictive of IADL above and beyond executive dysfunction (e.g., complex attention, verbal fluency, and cognitive control), as well as a widely-used cognitive screening battery.…”
Section: Discussionmentioning
confidence: 99%
“…We also extend Smits et al (1997) by incorporating comparison tests of executive functions, which prior studies show are among the most reliable cognitive predictors of IADL in older adults (e.g., Lewis & Miller, 2007). Importantly, PM was predictive of IADL above and beyond executive dysfunction (e.g., complex attention, verbal fluency, and cognitive control), as well as a widely-used cognitive screening battery.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, as mentioned earlier, it is important to assess both cognitive and functional abilities within the geriatric population. Nevertheless, previous research has found that functional decline is strongly linked with executive decline (Bell-McGinty, Podell, Franzen, Baird, & Williams, 2002;Cahn-Weiner, Malloy, Boyle, Marran, & Salloway, 2000;Lewis & Miller, 2007;Mitchell & Miller, 2008;Sherod et al, 2009).…”
mentioning
confidence: 93%
“…In particular, executive function and IADLs were found to be significantly associated across normal controls, those with mild cognitive impairment (MCI), and those with Alzheimer's disease (Marshall et al, 2011). It is important to note that although there is an association between cognitive and functional decline, research shows that cognitive decline does not completely account for all of the loss in functional ability (Baird, 2006;Lewis & Miller, 2007;Sherod et al, 2009). Therefore, as mentioned earlier, it is important to assess both cognitive and functional abilities within the geriatric population.…”
mentioning
confidence: 99%
“…Research suggests that many cognitive factors contribute to functional impairment in older adult populations, including global cognitive functioning (Farias, Harrell, Neumann, & Houtz, 2003; Inzarti & Basile, 2003), memory (Farias, Mungas, Reed, Harvey, Cahn-Weiner, & DeCarli, 2006; McCue, Rogers, & Goldstein, 1990), processing speed (Tuokko, Morris, & Ebert, 2005; Teng, Becker, Woo, Knopman, Cummings, & Lu, 2010), visuoperceptual abilities (Glosser, Gallo, Duda, de Vries, Clark, & Grossman, 2002; Jefferson, Barakat, Giovannetti, Paul, & Glosser, 2006), and executive functioning (Bell-McGinty, Podell, Franzen, Baird, & Williams, 2002; Cahn-Weiner et al, 2000; Lewis & Miller, 2007). Within the older adult population, executive functioning (e.g., Mariani et al, 2008; Rapp & Reischies, 2005; Cahn-Weiner et al, 2000) and memory (e.g., Farias et al, 2006; Jefferson et al, 2008; Koehler et al, 2011; Teng et al, 2010) have been identified as the two cognitive domains most consistently related to everyday functioning.…”
mentioning
confidence: 99%